P215 The influence of age on management of lung cancer patients in England. (16th November 2010) - Beckett, P; Woolhouse, I; Peake, M D; Stanley, R; Harrison, R N
Abstract : Introduction: The evidence on which to base treatment decisions in the elderly patient with lung cancer is generally considered to be inadequate, with significant under-representation of older patients in key clinical trials. Although European recommendations have recently been published confirming the benefits of active treatment (EORTC Elderly Task Force), there are no UK guidelines and anecdotal evidence suggests that in the UK elderly patients have much lower rates of active treatment for lung cancer. Methods: Using the National Lung Cancer Audit dataset of 27 815 patients first seen in 2008, we have analysed a variety of measures according to patient age at the time of diagnosis. Patients outside the range 38–96 were excluded due to low numbers. Results: Comparison with Cancer Research-UK data shows that the elderly are not under-represented in the dataset; neither is there any evidence of under-reporting of key case-mix variables such as PS and Stage. Older patients tend to have lower stage at diagnosis, but this may be due to a reduced intensity of investigations. Not unexpectedly, there is a rapid decline in the proportion with good PS after age 70. Whilst FEV1 (absolute) declines with age, the average FEV1 % of predicted remains quite constant at around 70%. There is an increase in recording of co-morbidities from around 5% in young patients to around 20% in the very elderly. There is a clear and dramatic fall in a number of measures of process and treatment such as histological confirmation rate, anti-cancer treatment, and chemotherapy use beginning around the 7th decade of life. The histological confirmation rate falls from 75% at age 65 to 40% at age 85—the corresponding rates for specific anti-cancer therapy are 65% and 25%. More concerning is the finding that these variations persist when corrected for PS and co-morbidities (see Abstract P215 Figure 1 ), with treatment rates falling from 50% to 4%. Conclusions: Age appears to be an important factor in management decisions in English lung cancer practice. The results indicate that further work is warranted to determine how far the results can be explained by patient preference, appropriate physician judgement and physician prejudice.